Alienation in Contemporary Sculpture between the Works of Anthony Caro and Tony Cragg (A Comparative Study) (Al-Academy, 2018)
The subject of this research is the study of the formal alienation of contemporary English sculpture, by comparing the most important sculptors of the new contemporary generation. This research problem is to look for the important factors in the formation of the contemporary sculptural structure of the exotic, and what is the mechanism of formation and output of these forms. The research seeks to explore (Alienation in contemporary sculpture between the works of Anthony Caro and Tony Cragg) in a comparative study. The importance of the research is to identify the concept of alien forms in contemporary British sculpture, especially in the cases of Anthony Caro and Tony Cragg that this research is considered a knowledge research that has importance in highlighting the construction of contemporary sculptural form, and the processes of alienation in the plastic art achievement.The temporal and spatial limits of the research are from 1965 to 2014 with all the materials, methods and techniques of modern sculpture in Britain. It also included a definition of the terms used in it, and it is made of two sections, the concept of alienation in thought, which addressed the most important intellectual and philosophical approaches that were a major cause of alienation of the new form or they called for it. The second section involves the alienation in the sculptural form and deals with the exotic forms of ancient and contemporary history and the formal transformation of the stage. The methodological framework included research procedures, i.e., the research community, sample, methodology, and justification for the selection of four samples. They were chosen in accordance with the rationale of their representation of the research community and its temporal limitations through which the purpose of the research is reached after analyzing them and getting the most important results and conclusions and discussing them including:The alienation in the works of the sculptors through the first new production of each sculptor was shown at the beginning of any new experiment. These shapes are new and strange to his other shapes and also strange to the surrounding productions produced by the British sculptors. Thus the alienation was represented in form, technique, material, style, concept, presentation and installation of elements. The alienation has been shown in a specific time and place, and the exotic works have exceeded that time and place in their style, form, techniques. The exotic presentation methods are governed by a specific time and place because each product after passing the temporal or spatial period becomes a naïve subject that has been consumed because of the many experiments based on its concept, idea or style